Pengaruh Label Halal, Brand Image, Kualitas Produk, Dan Jasa Endorse Terhadap Keputusan Pembelian Kosmetik Sariayu (Studi Pada Ibu-ibu di Desa Lesanpuro) - Widiatus Sholiha; Muhammad Ridwan Basalamah; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to examine the effect of halal label, brand image, product quality andservices endorsed on the purchasing decision of Sariayu cosmetics. The population in this study were women in Lesanpuro. The sample selection is mothers who have and are currently using Sariayu cosmetics. In this study using atechnique purposive side. The number of samples used as many as 120 mothers. The analytical technique used in this research is multiple linear regression analysis technique with quantitative methods. The results of this study indicate that (1) halal labels, brand image, product quality, andservices endorse simultaneously have a positive and significant effect on purchasing decisions (2) halal labels partially affect purchasing decisions (3) purchasing decisions. brand image partially has no effect onpurchasing decisions (4) product quality partially has no effect on purchasing decisions (5) services endorse partially affect purchasing decisions. Keywords : Halal Label, Brand Image, Product Quality And Services Endorsed